Low cost and portable software defined radio ground station - Ojur, Barbara Apili (Department of Electrical Engineering, 2020)
Small satellites are being launched by a multitude of private and public organizations around the world. They are innately cheaper than their large counterparts. This attribute, and additional ones, such as their easy-to-assemble nature and the convenience of using commercially available off-the-shelf parts to build them has enhanced their popularity. Now that getting into space has become more accessible there is an influx of information available from small satellites, however the information is not being utilized too efficiently on Earth. One reason as to why this is evident is because traditional ground stations, which are largely hardware dependent, are expensive to develop. However, with the introduction of Software Defined Radios (SDRs) many of the operations formerly done using hardware can now be implemented in software. Using a SDR can substantially reduce the cost of a traditionally hardware-based ground station. A number of universities and other organizations have or are developing SDR ground stations to communicate with satellites in different orbits. The ability to receive or transmit signals is important because it displays the capability to develop and operate satellites to various stakeholders. This dissertation attempted to enhance the movement towards satellite communication using SDR technology by developing a low cost, portable, easy to assemble and extendable ground station at the University of Cape Town in order to make contact with one or more small satellites in Low Earth Orbit (LEO), to encourage data usage, national and international collaboration and education. The ground station was constructed and tested based on its objectives, requirements and constraints. The commissioning tests were conducted in the SpaceLab at the University of Cape Town. The ground station was able to make contact with two small satellites in LEO successfully. Packets were received from two satellites that clearly stated who they were. The information contained in the packets was decoded into ASCII text and Hex code. They were compared with other successful amateur ground station results from all over the world to verify their authenticity. The main conclusion was that the SDR ground station was able to make contact with small satellites in LEO operating in the 70-cm band.